FATIGUE LIFE ANALYSIS OF SHEARER PICKS BASED ON LOAD RECONSTRUCTION THEORY - MAO Jun; WANG Xin; CHEN HongYue; ZHANG Yu (Jixie qiangdu)
In order to study the fatigue life of the shearer’pick in the actual working conditions,the load was reconstructed by using the analytical continuation principle. The method of the conjugate gradient method was used to solve the reconstruction function. Using ANSYS Workbench transient dynamic analysis on the dynamics of the shearer drum, and will be the reconstruction of load loaded in the form of the time sequence to pick,the results file to import ncode of pick and pick-seat life prediction and simulation results show that: Life parts minimum zone appears in pick-seat and shearer drum blade welding,in drum pick in cutting coal and rock,pick-seat and a blade welding premises by the stress,and the existence of the phenomenon of stress concentration,welding to eliminate residual stress and grinding process.